World Music in Fusion at the Margravial Opera House Bayreuth | October 31, 2019 (Conference 2019, 2020)
The Africa Mulitple Cluster of Excellence's kick-off conference held between 30 and 31 October 2019 came to a festive close with a concert featuring musicians from three continents. The renowned musicians EunKyung Kim and JaeHyo Chang from Korea, Childo Tomas and Matchume Zango from Mozambique and Tao Ravao from Madagascar came together for the sole purpose of this concert creating songs especially for that occasion. The Baroque stage of the Margravial Opera House in Bayreuth – named a UNESCO world heritage site in 2012 – provided the unique and extraordinary stetting for this once in a lifetime event. - Follow us on Social Media: Facebook - https://www.facebook.com/pg/AfricaMultiple Instagram - https://www.instagram.com/exc2052/ Twitter - https://twitter.com/ClusterAfrica https://www.africamultiple.uni-bayreuth.de/